Kinetic and mechanistic studies on aldehyde dehydrogenases from sheep liver : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Chemistry at Massey University, New Zealand - Bennett, Adrian F. (Massey University, 1981)
The mechanisms of sheep liver aldehyde dehydrogenases have been further investigated by both steady-state and pre-steady-state kinetic methods. By utilizing the acid/base indicator phenol red, a burst in the production of protons has been detected for both the cytoplasmic and mitochondrial isoenzymes. The rates and amplitudes of the two proton bursts were almost identical to those for the NADH bursts which both isoenzymes exhibit. After a consideration of the kinetic data, the electronic structure of various aldehydes and computer simulation studies, the proton burst process was postulated as arising from a conformational change on aldehyde binding to the enzyme-NAD + binary complex. The proton release arises from the perturbation of the pKa of a protonated functional group from about 8.5 to below 5.0 The effects of the Mg 2+ ion on the cytoplasmic isoenzyme were also studied. The presence of millimolar concentrations of this ion resulted in marked inhibition of the enzyme activity, and a lowering of the dissociation constants for both the E.NAD + and E.NADH binary-enzyme complexes. Steady-state and pre-steady-state studies showed that the major effect of MgCl 2 on the enzyme mechanism was to slow the steady-state rate-limiting step, which was NADH dissociation at high propionaldehyde concentrations and an unidentified step, possibly involving deacylation, at low propionaldehyde concentrations.
Keywords: Aldehydes; Liver -- Physiology